CARD15/NOD2 polymorphisms differ among Polish Crohn’s disease (CD) and differentiated thyroid cancer (DTC) patients (International Journal of Medicine and Medical Sciences, 2011)
Recent studies proved that mutations in the CARD15/NOD2 gene can increase the risk for different malignancies, e.g. bowel, lung and breast cancer. Although many correlations between CARD15/NOD2 and malignancies have been investigated, so far no association between inflammatory bowel diseases and differentiated thyroid cancer (DTC) among Polish patients have been done. The aim of this study was to investigate two polymorphisms in CARD15/NOD2 gene: rs2066842 (p.Pro268Ser, c.802C>T), rs2066845 (p.Gly908Arg, c.2722G>C) and one frameshift mutation rs5743293 (p.Leu1007fsinsC, c.3019_3020insC) among two groups of patients: Crohn’s disease and differentiated thyroid cancer. A total of 591 individuals were enrolled in this study: 193 DTC patients (35 men and 158 women), 185 CD patients (96 women, 89 men) and 213 individuals in population group (107 male and 106 female). Genotyping and statistical analysis for all the investigated individuals was performed. This study confirmed the results obtained in previous investigations about the role of CARD15/NOD2 gene in CD, but did not revealed relations between CARD15/NOD2 gene and DTC.